European active surveillance study of women taking HRT (EURAS-HRT): study protocol [NCT00214903] - Heinemann Lothar AJ; Dinger Juergen C (BMC, 2006)
Abstract Background The post marketing safety surveillance program for a drug containing a new chemical entity should assess both, the safety outcomes that relate specifically to the targeted population, as well as those that could potentially be related to special pharmacological characteristics of the drug. Active safety surveillance using valid epidemiological study designs has been proven to be a pertinent and reliable method to approach this endeavor. Methods/design The primary objective of the study is to compare incidence rates of serious adverse events in users of all types of newly prescribed oral HRT products. This active surveillance study will assess pertinent cardiovascular outcomes - in particular venous and arterial thromboembolism - and other serious adverse events (SAEs) in new HRT users over a period of several years. One product under surveillance is Angeliq®, which contains the novel progestagen drospirenone (DRSP) combined with estradiol. In addition, all other oral combined HRT products with a novel progestagen or estrogen that will be newly marketed during the study period will be studied. These new HRT products will be compared with established HRT products. The combined cohort will include at least 30,000 women recruited in several European countries. At least 90,000 years of observation are expected from the field work which started in early 2002 and will end around 2008. The participating women will complete a baseline survey using a self-administered questionnaire to describe the baseline risk. After 6 months, 12 months, and then on an annual basis, they will fill out a questionnaire in which they record complaints and events during the use of the prescribed HRTs. All adverse outcomes occurring during the observational period will be evaluated. Discussion A complete lifetime medical history, individually validated SAEs over time, and a low loss to follow-up rate are essential for a robust safety assessment. Therefore, the lifetime history of diseases and relevant medications will be documented. Reported SAEs will be validated and analyzed. A four level, multi-faceted follow-up process was established to ensure low loss to follow-up rates (e.g., 3-5% after three years of follow up). Multivariate methods will be used to adjust for confounding.